2019
DOI: 10.1103/physreva.100.063405
|View full text |Cite
|
Sign up to set email alerts
|

Distance scaling and polarization of electric-field noise in a surface ion trap

Abstract: We probe electric-field noise in a surface ion trap for ion-surface distances d between 50 and 300 µm in the normal and planar directions. We find the noise distance dependence to scale as d −2.6 in our trap and a frequency dependence which is consistent with 1/f noise. Simulations of the electric-field noise specific to our trap geometry provide evidence that we are not limited by technical noise sources. Our distance scaling data is consistent with a noise correlation length of about 100 µm at the trap surfa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…different secular frequencies. It was found that the dependence of the heating rates on the secular frequencies is not consistent with a proper power-law behavior, as would be expected for anomalous heating originating from surface heating 85 . This indicates that at least the transverse modes are predominantly affected by technical noise.…”
Section: Ion Heatingmentioning
confidence: 77%
“…different secular frequencies. It was found that the dependence of the heating rates on the secular frequencies is not consistent with a proper power-law behavior, as would be expected for anomalous heating originating from surface heating 85 . This indicates that at least the transverse modes are predominantly affected by technical noise.…”
Section: Ion Heatingmentioning
confidence: 77%
“…We can normalize our measured heating rate for ion mass and trap frequency to compare with community data [16,21,22]. To do so, we consider the heating rate given by ṅ = q 2 4m ω S E where q is the charge of the ion, m is the mass of the ion, ω is the motional frequency, [14,15,22].…”
Section: Heating Ratesmentioning
confidence: 99%
“…Figure 5 shows our results as we scan the frequency from 2π×2.5 The heating rate has been normalized for ion mass and secular motional trap frequency. We plot our data as the green star compared to previously published data from [14] (black circles), [22] (blue squares), and [15] (red diamonds). The scaling of each fit is indicated in the legend.…”
Section: Heating Ratesmentioning
confidence: 99%
“…where f (T ) is a function of the temperature. 4 Although aspects of this functional form and its exponents are still a subject of debate, 4,24 most experiments point to a frequency scaling involving an α of between 0 and 2 at MHz frequencies. 3,[25][26][27][28][29] This scaling is in line with the practical experience that most sources of noise have a "1/ω" character with α = 1.…”
Section: Introductionmentioning
confidence: 99%